A Saccharomyces cerevisiae bio-databank for winemaking strain selection - Vieira, E. (2010)
The winemaking industry faces currently an increased demand for novel Saccharomyces cerevisiae strains that are well adapted to different wine styles and that contribute to improved aromatic characteristics. In this reasoning, the Centro de Biologia Molecular e Ambiental (CBMA) at the University of Minho gathered one of the largest bio-databanks of S. cerevisiae, obtained from winemaking environments in Portugal and France. During the harvest time of 2001 to 2009, 604 grape samples were collected in appellations of origin in Portugal (Vinho Verde, Dão, Douro, Bairrada, Estremadura, Palmela, Ribatejo, Açores) and France (Languedoc). The grape samples belonged to the varieties Alvarinho, Aragonez, Arinto, Avesso, Baga, Bical, Castelão, Carignan, Loureiro, Maria Gomes, Terrantez, Touriga Nacional and Verdelho. Yeast populations, in particular S. cerevisiae, were isolated after spontaneous fermentation of the extracted grape juice. From the final stage of 258 fermentations, 7740 yeast isolates were obtained, belonging mainly (5496 isolates) to the species S. cerevisiae. An initial genetic screen, based on mitochondrial DNA restriction fragment length polymorphism (mtDNA RFLP), electrophoretic karyotyping or interdelta sequence analysis, was followed by microsatellite analysis of 6 polymorphic microsatellite loci. Isolates were assigned to 752 different strains, based on their microsatellite allelic distribution. The collection of 752 autochthonous S. cerevisiae strains is a valuable resource for the selection of winemaking strains, biodiversity preservation and equitable sharing of genetic data. Within ongoing research, novel strains are selected to enhance aromatic profiles of specific wines.